61.2.68 problem 68
Internal
problem
ID
[12074]
Book
:
Handbook
of
exact
solutions
for
ordinary
differential
equations.
By
Polyanin
and
Zaitsev.
Second
edition
Section
:
Chapter
1,
section
1.2.
Riccati
Equation.
1.2.2.
Equations
Containing
Power
Functions
Problem
number
:
68
Date
solved
:
Tuesday, January 28, 2025 at 12:14:08 AM
CAS
classification
:
[_rational, _Riccati]
\begin{align*} x^{2} \left (x +a \right ) \left (y^{\prime }+\lambda y^{2}\right )+x \left (b x +c \right ) y+\alpha x +\beta &=0 \end{align*}
✓ Solution by Maple
Time used: 0.005 (sec). Leaf size: 1508
dsolve(x^2*(x+a)*(diff(y(x),x)+lambda*y(x)^2)+x*(b*x+c)*y(x)+alpha*x+beta=0,y(x), singsol=all)
\[
\text {Expression too large to display}
\]
✓ Solution by Mathematica
Time used: 3.315 (sec). Leaf size: 1770
DSolve[x^2*(x+a)*(D[y[x],x]+\[Lambda]*y[x]^2)+x*(b*x+c)*y[x]+\[Alpha]*x+\[Beta]==0,y[x],x,IncludeSingularSolutions -> True]
\begin{align*}
y(x)\to \frac {2 a \left (a-c+\sqrt {a^2-2 (c+2 \beta \lambda ) a+c^2}\right ) \operatorname {Hypergeometric2F1}\left (\frac {-c+a \left (b-\sqrt {b^2-2 b-4 \alpha \lambda +1}\right )+\sqrt {a^2-2 (c+2 \beta \lambda ) a+c^2}}{2 a},\frac {-c+a \left (b+\sqrt {b^2-2 b-4 \alpha \lambda +1}\right )+\sqrt {a^2-2 (c+2 \beta \lambda ) a+c^2}}{2 a},\frac {a+\sqrt {a^2-2 (c+2 \beta \lambda ) a+c^2}}{a},-\frac {x}{a}\right ) x^{\frac {\sqrt {a^2-2 (c+2 \beta \lambda ) a+c^2}}{a}}-\frac {\left (-c+a \left (b-\sqrt {b^2-2 b-4 \alpha \lambda +1}\right )+\sqrt {a^2-2 (c+2 \beta \lambda ) a+c^2}\right ) \left (-c+a \left (b+\sqrt {b^2-2 b-4 \alpha \lambda +1}\right )+\sqrt {a^2-2 (c+2 \beta \lambda ) a+c^2}\right ) \operatorname {Hypergeometric2F1}\left (\frac {-c+a \left (b-\sqrt {b^2-2 b-4 \alpha \lambda +1}+2\right )+\sqrt {a^2-2 (c+2 \beta \lambda ) a+c^2}}{2 a},\frac {-c+a \left (b+\sqrt {b^2-2 b-4 \alpha \lambda +1}+2\right )+\sqrt {a^2-2 (c+2 \beta \lambda ) a+c^2}}{2 a},\frac {\sqrt {a^2-2 (c+2 \beta \lambda ) a+c^2}}{a}+2,-\frac {x}{a}\right ) x^{\frac {a+\sqrt {a^2-2 (c+2 \beta \lambda ) a+c^2}}{a}}}{a+\sqrt {a^2-2 (c+2 \beta \lambda ) a+c^2}}+2 a^{\frac {a+\sqrt {a^2-2 (c+2 \beta \lambda ) a+c^2}}{a}} c_1 \left (\frac {\left (c+a \left (\sqrt {b^2-2 b-4 \alpha \lambda +1}-b\right )+\sqrt {a^2-2 (c+2 \beta \lambda ) a+c^2}\right ) \left (c-a \left (b+\sqrt {b^2-2 b-4 \alpha \lambda +1}\right )+\sqrt {a^2-2 (c+2 \beta \lambda ) a+c^2}\right ) \operatorname {Hypergeometric2F1}\left (-\frac {c+a \left (-b+\sqrt {b^2-2 b-4 \alpha \lambda +1}-2\right )+\sqrt {a^2-2 (c+2 \beta \lambda ) a+c^2}}{2 a},-\frac {c-a \left (b+\sqrt {b^2-2 b-4 \alpha \lambda +1}+2\right )+\sqrt {a^2-2 (c+2 \beta \lambda ) a+c^2}}{2 a},2-\frac {\sqrt {a^2-2 (c+2 \beta \lambda ) a+c^2}}{a},-\frac {x}{a}\right )}{2 a \left (\sqrt {a^2-2 (c+2 \beta \lambda ) a+c^2}-a\right )}-\frac {\left (-a+c+\sqrt {a^2-2 (c+2 \beta \lambda ) a+c^2}\right ) \operatorname {Hypergeometric2F1}\left (-\frac {c+a \left (\sqrt {b^2-2 b-4 \alpha \lambda +1}-b\right )+\sqrt {a^2-2 (c+2 \beta \lambda ) a+c^2}}{2 a},-\frac {c-a \left (b+\sqrt {b^2-2 b-4 \alpha \lambda +1}\right )+\sqrt {a^2-2 (c+2 \beta \lambda ) a+c^2}}{2 a},1-\frac {\sqrt {a^2-2 (c+2 \beta \lambda ) a+c^2}}{a},-\frac {x}{a}\right )}{x}\right ) x}{4 a^2 x \lambda \left (c_1 \operatorname {Hypergeometric2F1}\left (-\frac {c+a \left (\sqrt {b^2-2 b-4 \alpha \lambda +1}-b\right )+\sqrt {a^2-2 (c+2 \beta \lambda ) a+c^2}}{2 a},-\frac {c-a \left (b+\sqrt {b^2-2 b-4 \alpha \lambda +1}\right )+\sqrt {a^2-2 (c+2 \beta \lambda ) a+c^2}}{2 a},1-\frac {\sqrt {a^2-2 (c+2 \beta \lambda ) a+c^2}}{a},-\frac {x}{a}\right ) a^{\frac {\sqrt {a^2-2 (c+2 \beta \lambda ) a+c^2}}{a}}+x^{\frac {\sqrt {a^2-2 (c+2 \beta \lambda ) a+c^2}}{a}} \operatorname {Hypergeometric2F1}\left (\frac {-c+a \left (b-\sqrt {b^2-2 b-4 \alpha \lambda +1}\right )+\sqrt {a^2-2 (c+2 \beta \lambda ) a+c^2}}{2 a},\frac {-c+a \left (b+\sqrt {b^2-2 b-4 \alpha \lambda +1}\right )+\sqrt {a^2-2 (c+2 \beta \lambda ) a+c^2}}{2 a},\frac {a+\sqrt {a^2-2 (c+2 \beta \lambda ) a+c^2}}{a},-\frac {x}{a}\right )\right )} \\
y(x)\to \frac {\frac {a \left (c^2-2 a (2 \beta \lambda +c)\right ) \left (\sqrt {a^2-2 a (2 \beta \lambda +c)+c^2}-a+c\right )}{x}-\frac {\left (2 \alpha a^3 \lambda +a^2 \left (2 \alpha \lambda \sqrt {a^2-2 a (2 \beta \lambda +c)+c^2}+4 b \beta \lambda +b c-2 \beta \lambda \right )-a \left (b c \sqrt {a^2-2 a (2 \beta \lambda +c)+c^2}+2 \beta \lambda \sqrt {a^2-2 a (2 \beta \lambda +c)+c^2}+b c^2+c^2+4 \beta c \lambda \right )+c^2 \left (\sqrt {a^2-2 a (2 \beta \lambda +c)+c^2}+c\right )\right ) \operatorname {Hypergeometric2F1}\left (-\frac {c+a \left (-b+\sqrt {b^2-2 b-4 \alpha \lambda +1}-2\right )+\sqrt {a^2-2 (c+2 \beta \lambda ) a+c^2}}{2 a},-\frac {c-a \left (b+\sqrt {b^2-2 b-4 \alpha \lambda +1}+2\right )+\sqrt {a^2-2 (c+2 \beta \lambda ) a+c^2}}{2 a},2-\frac {\sqrt {a^2-2 (c+2 \beta \lambda ) a+c^2}}{a},-\frac {x}{a}\right )}{\operatorname {Hypergeometric2F1}\left (-\frac {c+a \left (\sqrt {b^2-2 b-4 \alpha \lambda +1}-b\right )+\sqrt {a^2-2 (c+2 \beta \lambda ) a+c^2}}{2 a},-\frac {c-a \left (b+\sqrt {b^2-2 b-4 \alpha \lambda +1}\right )+\sqrt {a^2-2 (c+2 \beta \lambda ) a+c^2}}{2 a},1-\frac {\sqrt {a^2-2 (c+2 \beta \lambda ) a+c^2}}{a},-\frac {x}{a}\right )}}{2 a^2 \lambda \left (2 a (2 \beta \lambda +c)-c^2\right )} \\
\end{align*}